Study of 60 obstructive arteriopathies of the lower limbs with ultrasound (Doppler effect) - Castro, Danilo; Balboa, Oscar; Lerena, Ana; Ricciardi, Norma; Ardao, Gonzalo; Matteucci, Pablo (Cirugía del Uruguay, 1982)
A prospective analysis of 60 patients with peripheral arterial failure of the lower limbs was carried out; the clinical manifestations, arteriography and the ultrasound hemodynarnic tests are compared. The authors emphasize the importance of the ultrasound test added to the functional study of the patient, together with arteriography. The ultrasound test becomes a valuable tool in the diagnosis of vascular patients, the· therapeutical decision, functional prognosis and follow up,